Factors influencing the unexpected measles outbreak of 2023 in Colombo, Sri Lanka - Kasunee Kalubowila; Chandana Gajanayake (Journal of the College of Community Physicians)
Introduction: Measles, a highly contagious viral disease remains a significant global public health concern. The resurgence of measles outbreak in 2023 ended the four-year measles-free status in Sri Lanka initially achieved in 2019. Objectives: To examine the risk factors contributing to the unexpected outbreak in the Colombo Regional Director of Health Services (RDHS) area and offer recommendations for public health implications Methods: A cross-sectional study was conducted among all 142 notified cases of fever and maculopapular rash reported for one-year from 1 January 2023 in Colombo RDHS area. Cases were confirmed based on serological, virological, clinical or epidemiological criteria, with incomplete data revisited to ensure accuracy. Information on demographic data, vaccination status, and contact history was collected. Odds ratio (OR) with 95% confidence interval (CI) was calculated to identify risk factors, and multiple logistic regression was performed to adjust for confounders. A p-value of less than 0.05 was considered statistically significant. Results: Of the 142 notified cases of fever and maculopapular rash, 113 were confirmed as measles (79.6%). Of the confirmed cases, 80 (70.8%) were confirmed through blood, throat, or nasal swab testing, 33 (29.2%) were clinically confirmed, and 2 (1.8%) were confirmed based on epidemiological criteria. Among the confirmed cases, 48.7% (n=55) were aged between 3-15 years, and 55.8% (n=63) were female. The highest proportion of cases was identified within the Muslim population (53.1%). A majority (n=92; 81.4%) of confirmed cases were unvaccinated. A history of contact with infected individuals significantly increased the risk of measles (OR=7.50; 95% CI: 2.10-14.4; p=0.002). Children aged 3 years or younger exhibited a lower risk (OR=0.41; 95% CI: 0.25-0.68; p=0.001), while vaccination demonstrated strong protection against infection (OR=16.61; 95% CI: 3.38-20.48; p=0.001). Contact history (adjusted OR=8.46) and non/partial vaccination (adjusted OR=6.61) were the strongest predictors of infection. Conclusions & Recommendations: Measles outbreak in 2023 was predominantly driven by unvaccinated individuals and contact with infected cases. To prevent future outbreaks and enhance immunization coverage, targeted catch-up immunization campaigns focusing on high-risk groups, alongside culturally sensitive educational initiatives are urgently required.